Performance musical cantada para Surdos: interpretando a canção de câmara brasileira - Andréa Peliccioni Sobreiro (2023)
This research addresses the creation of a sung and sign language musical performance in Brazilian Sign Language (Libras), intended for a heterogeneous audience composed of Deaf and hearing individuals, with special attention to the enjoyment of the Deaf audience, often distant from music appreciation spaces. We sought to find means that could contribute to and offer this target audience a broader and more effective artistic, aesthetic, and sensory experience. In this proposal for a musical performance, we considered the realization by the figure known as the “Cantorsinalizante”, believing that this could foster closer connections between the performer, the audience, and the work, expanding the semantic and sensory possibilities of the musical and textual elements of the songs. As the corpus of this research, four art songs by the Brazilian composer Edmundo Villani-Côrtes were selected for performance: Valsinha de roda (1979), Papagaio azul (1999), Pai Nosso (2001), and Rosa Amarela (2022). Based on the composer's narratives, the songs were translated, recreated, and reinterpreted in the musical performance, leading to the creation of the so-called “Canções de Ver”. The theoretical foundation for the development of this proposal included principles of semiology, with an emphasis on Jan Molino's tripartite theory developed by Jean Jacques Nattiez, advancing to Intermediality theories based on studies by Irina Rajewsky, Thierry Groensteen, Lars Elleström, and Linda Hutcheon. Additionally, concepts of narrativity and musical narrative, as discussed by Tarasti and John Rink, contributed to the creation of the performances. To select the focus group for this research, we initially used a Google form and then a video invitation. Through these means, we were able to establish a group of 30 Deaf participants who evaluated the performance proposal. The data obtained pointed to the need for further in-depth studies on the use of sign language in the context of concert music, especially in sung musical performances. From these results, it was also evident that sung musical performances using sign language are still not widely known in Brazil, which in turn generates some discomfort among part of the target audience of this research. In the context of this thesis, the challenge of conducting research that includes sign language in sung musical performance, particularly in music research, was received quite satisfactorily. On one hand, it presents the possibility of becoming the first research on the topic conducted in Brazil, and on the other hand, the use of sign language in the context of concert music can contribute to a new perspective on the perception and reception of the song genre. With this proposal, we aimed to contribute to a differentiated and innovative sung musical performance that is widely accessible, interdisciplinary, and multimedia. It can be affirmed that this type of proposed performance is unprecedented in Brazil, especially in the realm of concert music.